Changes in plasma CXCL4 levels are associated with improvements in lung function in patients receiving immunosuppressive therapy for systemic sclerosis-related interstitial lung disease. Issue 1 (December 2016) - Volkmann, Elizabeth; Tashkin, Donald; Roth, Michael; Clements, Philip; Khanna, Dinesh; Furst, Daniel; Mayes, Maureen; Charles, Julio; Tseng, Chi-Hong; Elashoff, Robert; Assassi, Shervin
Abstract Background Increased circulatory levels of the chemokine CXCL4 have been associated with the presence of interstitial lung disease (ILD) in an observational study of patients with systemic sclerosis (SSc). The purpose of the present study was to evaluate the relationship between baseline CXCL4 level and extent of ILD in the context of a randomized controlled trial and to determine whether changes in CXCL4 levels in response to immunosuppression are associated with future progression of SSc-ILD. Methods A total of 142 SSc-ILD patients from Scleroderma Lung Study (SLS) II were randomized in a double-blind, parallel-arm trial, to receive mycophenolate (MMF) for 2 years or oral cyclophosphamide (CYC) for 1 year followed by 1 year of placebo. Plasma CXCL4 levels were measured at baseline, 12 months, and 24 months in SLS II participants (N = 136) and at a single time point in healthy controls (N = 67). A mixed-effects model evaluated the relationship between change in CXCL4 levels and SSc-ILD progression. The primary outcome was the course of the forced vital capacity. Results Baseline CXCL4 levels were significantly higher in SSc-ILD patients compared with healthy controls (2699 ± 1489 ng/ml vs 2233 ± 1351 ng/ml (mean ± SD);P = 0.019). However, no significant correlations were identified between CXCL4 levels and extent of ILD at baseline, as measured by the forced vital capacity, diffusing capacity of carbon monoxide, or radiographic extent of ILD. Plasma CXCL4 decreased significantly from baseline to 12 months in all patients (CYC:P < 0.001; MMF:P = 0.006) with no between-treatment differences (CYC vs MMF). Patients with the largest decline in CXCL4 levels during the first 12 months had an improved course of forced vital capacity %-predicted from 12 to 24 months (P = 0.040), even after adjusting for baseline disease severity and treatment arm assignment. Conclusions Levels of CXCL4 were higher in patients with SSc-ILD compared with controls and decreased in all patients treated with immunosuppressive therapy. While CXCL4 levels were not correlated with extent of ILD at baseline, changes in CXCL4 at 12 months predicted future progression of SSc-ILD from 12 to 24 months. These findings suggest that intermediate-term changes in CXCL4 may have predictive significance for long-term progression of SSc-ILD in patients receiving immunosuppressive therapy. Trial registration ClinicalTrials.govNCT00883129 . Registered 16 April 2009.